Development of Android-Based Interactive Multimedia On Thematic Learning - Anna Pertiwi; Kamal Kamal; Hamdi M. Daming; Muhammad Takdir; Hariyanti Hamid (Departement of Mathematics Education, 2023)
This research and development were conducted at SD Madrasah Ibtidaiyah Muhammadiyah using the ADDIE development model. The model consists of analysis, design, development, implementation, and evaluation stages. The result of this research is an interactive multimedia product based on the Android platform for thematic learning, specifically focusing on the subject of national historical events during the colonial era, intended for elementary school fifth-grade students with a focus on the Social Studies subject.The interactive multimedia based on Android was developed using Unity and Photoshop applications, incorporating text, images, and sound components. This multimedia can be downloaded and installed on Android-based smartphones. The product testing results showed that the validation by media experts reached 85.30%, while the validation by subject matter experts reached 95.45%. The average of these two validations falls into the category of highly valid. The effectiveness test through evaluation questions yielded a result of 96.24%, which falls into the category of highly effective and achieved a high level of completion. The practicality test obtained a percentage of 96.7% from teachers and 96.30% from students, which falls into the category of highly practical. The attractiveness test yielded a percentage of 96.72% from students, also falling into the category of highly attractive.Therefore, based on the above presentation, it can be concluded that the interactive multimedia based on Android for thematic learning on the topic of national historical events during the colonial era is suitable for use in elementary school fifth-grade students. This product meets the criteria of being valid, effective, practical, and attractive.